A Convolutional and Recurrent Neural Network-based Approach for Speech Emotion Recognition - Duch, Piotr; Wiatrowska, Izabela; Kapusta, Paweł (Wydawnictwo Politechniki Łódzkiej, 2023)
Speech emotion recognition (SER) is a crucial aspect of humancomputer interaction. In this article, we propose a deep learning approach, using CNN and RNN architectures, for SER using both convolutional and recurrent neural networks. We evaluated the approach on four audio datasets, including CREMA-D, RAVDESS, TESS, and EMOVO. Our experiments tested various feature sets and extraction settings to determine optimal features for SER. Our results demonstrate that the proposed approach achieves high accuracy rates and outperforms state-of-the-art algorithms.
Keywords: artificial intelligence; speech emotion recognition; sztuczna inteligencja; rozpoznawanie emocji mowy